Plutella australiana (Lepidoptera, Plutellidae), an overlooked diamondback moth revealed by DNA barcodes - Jean-Francois Landry (ZooKeys, 2013)
The genus Plutella was thought to be represented in Australia by a single introduced species, P. xylostella (Linnaeus), the diamondback moth. Its status as a major pest of cruciferous crops, and the difficulty in developing control strategies has motivated broad-ranging studies on its biology. Prior genetic work has generally supported the conclusion that populations of this migratory species are connected by substantial gene flow. However, the present study reveals the presence of two genetically divergent lineages of this taxon in Australia. One shows close genetic and morphological similarity with the nearly cosmopolitan Plutella xylostella. The second lineage possesses a similar external morphology, but marked sequence divergence in the barcode region of the cytochrome c oxidase I gene, coupled with clear differences in genitalia. As a consequence, members of this lineage are described as a new species, P. australiana Landry & Hebert, which is broadly distributed in the eastern half of Australia.